HEALING OF DIABETIC AND THERMAL WOUNDS BY HERBAL CREAM, IH-WH4 AND HERBERIN - S Chatterjee; A T Rao; S N Das (Indian Journal of Plastic Surgery)
The wound healing efficacy of IH-WH4 and HERBERIN was evaluated in diabetic and burn wound subjects. Histopathological studies revealed that administration of these two products hastened the formation of granulation tissue alongwith angiogenesis and fibroplasia.